Адвокатура и государство: [монография] / Ю. И. Стецовский - Стецовский Юрий Исаакович (Юристъ, 2007)
Экземпляры: аб. (2007) / Инвентарный номер: 50729 / Цена: / Сис.шифр: 67.75(2Рос) / Авт.знак: С 79 / ГРНТИ: 10.71.61 / ББК: 67.75(2Рос)